Letter from S. Feier to R. Pat Connor - Feier, S. (1951)
This letter from S. Feier of Buffalo Apparatus Corporation provides an outsider perspective on competition for Beckman Instruments' DR Spectrophotometer market, with specific mention of the Fisher Spectrocord.
Keywords: Ultraviolet spectroscopy; Scientific apparatus and instruments; Spectrophotometer; Beckman Instruments, Inc.